2018
DOI: 10.1093/bioinformatics/bty499
|View full text |Cite
|
Sign up to set email alerts
|

pyTFA and matTFA: a Python package and a Matlab toolbox for Thermodynamics-based Flux Analysis

Abstract: SummarypyTFA and matTFA are the first published implementations of the original TFA paper. Specifically, they include explicit formulation of Gibbs energies and metabolite concentrations, which enables straightforward integration of metabolite concentration measurements.MotivationHigh-throughput analytic technologies provide a wealth of omics data that can be used to perform thorough analyses for a multitude of studies in the areas of Systems Biology and Biotechnology. Nevertheless, most studies are still limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
157
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(157 citation statements)
references
References 22 publications
0
157
0
Order By: Relevance
“…The lack of a methodology that allows integrating fluxomics, thermodynamic constraints, metabolomics, and transcriptomics simultaneously into a GEM motivated us to develop TEX-FBA. The TEX-FBA formulation is based on the iMAT methodology [32,33] and extends it with the integration of thermodynamic constraints [25,26,50] and a new definition of flux ranges consistent with gene expression. The implementation of TEX-FBA follows a sequence of eight steps:…”
Section: The Tex-fba Formulation and Maximum Consistency Score (Mcs)mentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of a methodology that allows integrating fluxomics, thermodynamic constraints, metabolomics, and transcriptomics simultaneously into a GEM motivated us to develop TEX-FBA. The TEX-FBA formulation is based on the iMAT methodology [32,33] and extends it with the integration of thermodynamic constraints [25,26,50] and a new definition of flux ranges consistent with gene expression. The implementation of TEX-FBA follows a sequence of eight steps:…”
Section: The Tex-fba Formulation and Maximum Consistency Score (Mcs)mentioning
confidence: 99%
“…We solved FBA [22] with the version of the COBRA Toolbox v2.0 [56] included in the matTFA toolbox [50]. We performed TFA [25,26] with the matTFA toolbox [50]. We used MATLAB (R2016a and R2017a) and CPLEX (ILOG IBM v12.51 and v12.71) as the linear solver.…”
Section: Software Usage and Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the thermodynamic formulation [17] of the stoichiometric models D1, D2 and D3, we integrated fluxomics and metabolomics data for aerobically grown E.coli (S1 Table). Several assumptions were made on reaction directionalities, based on literature [14,[18][19][20][21], to further constrain the models (Methods).…”
Section: Thermodynamic-based Variability Analysismentioning
confidence: 99%
“…pyTFA (a Python package for thermodynamics‐based flux analysis [TFA]) and matTFA (a MATLAB toolbox) help include TFA in metabolic models to enable the integration of quantitative metabolomics data to study their effects on the net‐flux directionality of reactions in the network . Using both a reduced and a genome‐scale model of Escherichia coli , the authors demonstrated that TFA and data integration through TFA reduced the feasible flux space with respect to flux balance analyses (FBA).…”
Section: Miscellaneous Tools Of Interestmentioning
confidence: 99%